Inspiratory muscle training is effective in improving respiratory muscle functions in patients who have undergone coronary artery bypass graft - Praveen, Reshma; Swaminathan, Narasimman; Praveen, J.S (Medsportpress, 2009)
Background. Pulmonary complications are the most common cause of mortality and morbidity in post-operative populations, especially in cardiothoracic surgeries that may demand much attention from the therapist. Median sternotomy, a gold standard incision for CABG, has been shown to have an inevitable adverse effect on the performance of the respiratory muscles. Moreover, reduced blood supply to these muscles following the harvest of left internal mammary artery (LIMA) for CABG has been well acknowledged. The reduction in blood supply may lead to respiratory muscle weakness and affects recovery. In the recent past inspiratory muscle training has gained momentum as an acceptable technique in the rehabilitation of the respiratory muscles. To determine the effectiveness of inspiratory muscle training on respiratory muscle strength and endurance in patients who have undergone CABG with LIMA. Experimental study design with simple randomization Material and methods. Thirty patients who had undergone coronary artery bypass grafting with LIMA as one of the grafts were randomly divided into two groups. Postoperatively, the experimental group received inspiratory muscle training with a flow dependent trainer for 15 days exclusively along with the standard hospital protocol while the control group received only the standard physiotherapy protocol. The primary outcome measures were Maximum Inspiratory Pressure (PiMax) and Maximal Voluntary Ventilation (MVV), which are determinants of respiratory muscle strength and endurance, respectively. The variables were measured preoperatively, on the 4th day after the surgical procedure prior to training and 15 days after the training. Results. The inspiratory muscle strength and endurance in the interventional group showed significant improvement as compared to the control group. Also the MVV values in the interventional group reversed back to their presurgical levels and the improvement in the Pimax values of the experimental group was significantly higher than even the presurgical values. The control group did not display either of these two trends. Conclusions. The results of this study indicate that inspiratory muscle training is effective in improving the respiratory muscle strength and endurance in patients who have undergone coronary artery bypass graft. This study suggests that inspiratory muscle training represents a useful therapeutic adjunct in the rehabilitation protocol for patients who have undergone cardiac surgery.